Ad Hoc Networks for Cooperative Mobile Positioning - Rosa, Francescantonio Della; Leppäkoski, Helena; Ghalib, Ata-ul; Ghazanfari, Leyla; Garcia, Oscar; Frattasi, Simone; Nurmi, Jari (IntechOpen, 2011)
None